Az "új szakasz" gazdaságpolitikája Közép- és Kelet-Európában: ECONOMIC POLICY OF THE „NEW COURSE” IN CENTRAL AND EASTERN EUROPE - Endre, Domonkos (Közép-Európai Közlemények, 2021)
Sztálin halálát követő (1953. március 5.) időszakban hatalomra került új vezetés meghirdette az „új szakasz” politikáját, amely Georgij Malenkov miniszterelnök és munkatársai nevéhez kötődött. A korábbi korszakhoz képest módosították a gazdaságfejlesztés irányelveit, melynek során csökkentették a beruházásokon belül a nehézipar és a hadiipar arányát. A mezőgazdaságban felhagytak az erőszakos téeszesítéssel és szorgalmazták az élelmiszer-termelés növelését. Lényeges változást jelentett a sztálini időszakhoz képest, hogy a kommunista pártvezetés szakított a háború elkerülhetetlenségének koncepciójával és a személyi kultusz elvével. Az „új szakasz” bevezetésének szükségessége szorosan összekapcsolódott a szocialista tábor országaiban kialakult gazdasági és társadalmi feszültségekkel. Az enyhülési politika és a közép- és kelet-európai országok reformtörekvései szempontjából meghatározó fontosságú volt az SZKP 1956. február 14-25-ei XX. kongresszusa, amely szentesítette a desztalinizáció folyamatát. A sztálinista rendszert és annak bűneit elítélő hruscsovi politika jelentős hatást gyakorolt a közép- és kelet-európai államok későbbi gazdasági-politikai fejlődésére. After the death of Stalin on 5th March 1953, the new Soviet leadership headed by Malenkov and his associates launched the politics of “New Course”. Compared with the previous period, economic development policy was modified because the share of heavy and armament industries was reduced considerably within the investments. Measures were taken in the agriculture in order to lay off forced collectivization and to increase food processing. The communist leadership broke off with the Stalinist “cult of personality” and refused the concept of unavoidable war between East and West. The necessity for the introduction of the “New Course” was linked with the increasing economic and social tensions in the socialist countries. The political “thaw” and the reform endeavours of Central and Eastern Europe was influenced by the 20th Congress of the Soviet Communist Party, which was held in February of 1956. The speech of Nikita Khrushchev, who made a sharp turn against Stalinism, by condemning the violation of “socialist legality” and the ruthless terror had profound impact on the further economic and political development in the Central and Eastern European countries. As a result of this process de-Stalinisation started to emerge in the region as a whole. The objective of my paper is to analyse the peculiarities of the “New Course” in Central and Eastern Europe. Besides the comparison of the development of each country, emphasis will be given on the economic consequences of the political “thaw” in the region. Because of length constraints, I will not highlight the political history of Central and Eastern European countries.